How Arguments Work - A Guide to Writing and Analyzing Texts in College - Mills, Anna (Open textbook library., 2021)
How Arguments Work takes students through the techniques they will need to respond to readings and make sophisticated arguments in any college class. This is a practical guide to argumentation with strategies and templates for the kinds of assignments students will commonly encounter. It covers rhetorical concepts in everyday language and explores how arguments can build trust and move readers.